Value-driven approach for project success and change management in Malaysian Institutions of Higher Learning (IHL) - Faisal, Ammy Amelia; Safitri, Cutifa; Ahmad Dahlan, Abdul Rahman (International Journal of Science and Research, 2013)
As a project is a lifeline and strategic asset to any organization, identifying the critical success factors (CSFs) for the success of projects is vital in project management. This conceptual paper provides the literatures which have been made by various researchers regarding the project success factors and change management. The CSFs which have been applied and brought success to different organizations will be elaborated in order to identify the success factors that are relevant in Malaysian Institutions of Higher Learning (IHL context). Furthermore, the value-driven relationship which consider the three project elements, namely Business, Project Management Office (PMO), and Project Team have to be well understood. Lastly, the proposed framework involving the 3 project elements can lead to the success of project development, implementation and deployment which create value and competitive advantage, will be discussed as for the next step is to conduct the empirical study.